Optimizing Post-Cesarean Opioid Prescription Practices at Mayo Clinic: A Quality Improvement Initiative - Kim, Sharon; King, Amanda; Parikh, Pavan; Sangtani, Ajleeta; Shazly, Sherif; Brodrick, Ellen; Thompson, Angela (American Journal of Perinatology, 2021)
Objective Optimal prescriptions practices of opioids in the post-cesarean period remain controversial. The primary aim of this initiative was to minimize unused prescription narcotic medication, with a goal of ≤4 leftover pills of 5-mg oxycodone at postoperative day (POD) 14 without affecting pain or satisfaction measures.Study Design This was a prospective longitudinal quality improvement (QI) initiative starting in 2017 utilizing the DMAIC methodology. The measurement phase consisted of validated surveys over 3 months, along with chart review to determine current institutional prescription practices and predictors of outpatient opioid use. Resulting recommendations were adopted, and 1 year later, all patients undergoing cesarean were surveyed for 3 months to determine the effectiveness of the intervention. The study was approved by the Department's QI Committee.Results The response rate was 48%, with 50 of 101 patients completing surveys pre-intervention and 52 of 111 post-intervention. Pre-intervention, surplus medication was predicted (p <0.05) only by the quantity of the opioid prescription. In addition, patients who required ≤37.5 morphine milligram equivalents (MMEs) during the inpatient postoperative stay did not require outpatient narcotic prescriptions. Thereafter, a strategy of matching inpatient use to outpatient prescription 1:1 in a linear regression model (p <0.001, R2 0.55) optimally matched patient needs up to 200 MME. In the post-intervention survey, mean (SD) prescription decreased from 17.6 (13.7) MME to 8.4 (8.3) MME (p <0.01); 39% compared with 16% of women were discharged without a prescription (p <0.01); and amongst all patients 82.7% compared with 59.6% (p <0.01) had ≤4 pills remaining without differences in patient satisfaction or pain perception.Conclusion This initiative highlights a practical approach to QI utilizing industry techniques in health care. This approach resulted in significant reductions in over-prescription and unused medication, without impacting pain or satisfaction scores.Key Points
Keywords: cesarean; opioid; prescription; narcotic; pain relief